Detection of Tomato Mosaic Virus Viruses in Farms and Greenhouses and Breed Several Isolates of The Potato Virus Y From this Host - et al., Iman Abdel Sattar Abdel Razzaq (International Journal of Advanced Science and Technology, 2020)
Tomato is one of the most important vegetables in Iran and in many countries. This study examines the spread of mosaic virus viruses in farms and greenhouses in the 2017-2018 crop year. Our study region is located in Yazd county in Iran. In this study, we collected 451 leaf samples with signs of mosaic. To identify the viruses, we used tests of DAS-ELISA, ACP-ELISA, specific polyclonal antibodies of Potato virus Y(PVY), Cucumber mosaic virus (CMV), Tomato mosaic virus (ToMV) and Arabis mosaic virus (ArMV) and Potivirus single-stranded antibody. Percentage of contamination of specimens collected with putty virus, CMV, PVY, ArMV and ToMV were 35.9%, 11.3%, 20.6%, 2.6% and 13.5%, respectively. Therefore, according to the results, PVY is the predominant virus among the collected samples. Four species of potato Y virus were selected to investigate the breed type of the collected PVY isolates. After extracting total RNA from the contaminated isolates, a fragment of 837 bp was amplified using a PVY-specific protease region of the P1 protease region. To identify the strains studied, in the RFLP test, PCR product was affected by the Hinc test. Then, the pair of specific primers of PVY strains were used. The results of the reaction showed that all four isolates were NTN race.